Improved photoelectrochemical performance of tungsten-catalyzed graphene nanoplatelet electrodes prepared by hot-wire chemical vapor deposition at low substrate temperatures - Anuar, Nur Afira (Elsevier, 2024)
The current increase in demand for graphene in various energy applications such as electrode materials for supercapacitors, batteries, thermoelectric, and hydrogen production via water-splitting, the production of high-quality graphene, considering its fascinating physical and electrical properties, high-yield, and large-area has becoming more challenging at the research and development level. Therefore, in this work, graphene nanoplatelets (GNPs) were directly grown on tungsten nanoparticle (W NP)-coated p-type crystalline silicon and quartz substrates using hot-wire chemical vapor deposition at low substrate temperatures (<500 degrees C). Prior to the GNP deposition, a plasma process was employed to induce the formation of W NPs, which act as a metal catalyst for facilitating the growth of large-area and multi-layer GNPs. The W NPs were formed at substrate temperatures ranging from 250 to 550 degrees C, with the largest graphene sheet was grown at 450 degrees C. Higher substrate temperatures promote the growth of high-quality graphene layers with high intensities of G (I-G) and 2D bands (I-2D), and high I-2D/I-G ratio values. The GNP photoelectrode prepared at 450 degrees C demonstrated better photoelectrochemical responses with the highest photocurrent density of 1.65 mA/cm(2) at 1.5 V-Ag/AgCl, the lowest charge transfer resistance (14.0 k Omega), and the highest donor density (2.57 x 10 (28) cm(-3)) compared to the tungsten carbide thin film and W NP electrodes prepared at the same temperature. The effects of substrate temperature on the optical, structural, and photoelectrochemical properties of the as-grown GNPs are discussed.